Anatomy, histology, and systematic implications of the head ornamentation in the males of four species of Limnonectes (Anura: Dicroglossidae). (5th August 2014) - Lambertz, Markus; Hartmann, Timo; Walsh, Shannon; Geissler, Peter; McLeod, David S.
<x xml:space="preserve">Abstract</x> The males of four species of the Asian frog genus Limnonectes [Limnonectes dabanus (Smith, 1922a), Limnonectes gyldenstolpei (Andersson, 1916), Limnonectes macrognathus (Boulenger, 1917), and Limnonectes plicatellus (Stoliczka, 1873)] exhibit remarkable ornamentation in the form of a swollen, or cap‐like, structure (caruncle) on the top of their heads. These caruncles vary in their appearance among species, and neither their function nor their actual systematic value is known. We compared their anatomy via dissections, morphometrics, radiography, and histology, and analysed the available mitochondrial DNA sequences as well as new data to place these species within the context of a larger phylogenetic hypothesis for Limnonectes. Despite the externally different morphology, the underlying histological structure is virtually identical. Beneath skin that is densely packed with mucous glands lies a pad of connective tissue overlaying the parietal bone. The actual function of the caruncle, however, remains enigmatic. In addition to the presence of the caruncle, independent evidence from osteological characters and molecular data support the monophyly of a clade comprising of L. dabanus, L. gyldenstolpei, L. macrognathus, and L. plicatellus. The caruncles are therefore interpreted as a robust autapomorphy for this clade, and suggest that the subgenus Elachyglossa should be restricted to the four species in question. © 2014 The Linnean Society of London